2012
DOI: 10.2134/agronj2011.0292
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seeding Rate on Older Stands of Glyphosate‐Tolerant Alfalfa

Abstract: Increased seed cost of glyphosate tolerant (GT) compared to non-GT alfalfa (Medicago sativa L.) raises questions about reducing seeding rates. Th e objective of this study was to determine if alfalfa stand density, yield, and forage quality are compromised in the later years of the stand when reduced seeding rates, in combination with glyphosate application, were used during establishment. At seven locations in the United States, GT alfalfa was seeded into conventionally tilled seedbeds at 6.7, 11.2, 15.7, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Alfalfa has a great capacity to compensate for lost plants. Hall et al [6,18] reported plant density ranged between 120 to 200 plants m −2 in the sowing year, decreasing to less than 100 plants m −2 in the first production year. By the third production year, the plant density had decreased to less than 80 plants m −2 [18].…”
Section: Total Seasonal Forage Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Alfalfa has a great capacity to compensate for lost plants. Hall et al [6,18] reported plant density ranged between 120 to 200 plants m −2 in the sowing year, decreasing to less than 100 plants m −2 in the first production year. By the third production year, the plant density had decreased to less than 80 plants m −2 [18].…”
Section: Total Seasonal Forage Yieldmentioning
confidence: 99%
“…Hall et al [6,18] reported plant density ranged between 120 to 200 plants m −2 in the sowing year, decreasing to less than 100 plants m −2 in the first production year. By the third production year, the plant density had decreased to less than 80 plants m −2 [18]. The regression models for forage yield using plant density were significant (p ≤ 0.05) and similar for all years, utilizing both spring and fall plant density counts (Figure 3).…”
Section: Total Seasonal Forage Yieldmentioning
confidence: 99%
See 3 more Smart Citations